2008
DOI: 10.1080/02640410701567425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold water immersion on repeat cycling performance and thermoregulation in the heat

Abstract: To assess the effect of cold water immersion and active recovery on thermoregulation and repeat cycling performance in the heat, ten well-trained male cyclists completed five trials, each separated by one week. Each trial consisted of a 30-min exercise task, one of five 15-min recoveries (intermittent cold water immersion in 10 degrees C, 15 degrees C and 20 degrees C water, continuous cold water immersion in 20 degrees C water or active recovery), followed by 40 min passive recovery, before repeating the 30-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 38 publications
6
116
0
3
Order By: Relevance
“…Although cryotherapy is frequently used by athletes after intense exercise, only a few studies have assessed its effects on lactate recovery after intense exercise. Vaille et al 40 demonstrated that active recovery tended to improve lactate recovery over cryotherapy, whereas Crowe et al 9 found that lactate levels were lower with cryotherapy treatment compared to a control condition (passive rest). In our study, blood lactate increased 9% from exercise bout 1 to 3 during cryo, but was not different from the other interventions.…”
Section: Metabolic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cryotherapy is frequently used by athletes after intense exercise, only a few studies have assessed its effects on lactate recovery after intense exercise. Vaille et al 40 demonstrated that active recovery tended to improve lactate recovery over cryotherapy, whereas Crowe et al 9 found that lactate levels were lower with cryotherapy treatment compared to a control condition (passive rest). In our study, blood lactate increased 9% from exercise bout 1 to 3 during cryo, but was not different from the other interventions.…”
Section: Metabolic Markersmentioning
confidence: 99%
“…21 The available scientific evidence related to cold therapy and exercise performance is inconclusive. Some studies show a reduced exercise performance, 9,35 while others report an improved or maintained performance, 2,18,36,40,42 when cold water immersion is used as a recovery intervention and compared with passive recovery. The major limitation of the available studies is the lack of insight into mechanisms behind potential performance benefits or detriments to the use In the 15-to 60-minute period following exercise, lymphocyte counts tend to drop below resting values.…”
mentioning
confidence: 99%
“…Além disso, outros fatores como a depleção de substratos (principalmente glicogênio muscular), hipertermia e acúmulo de vários metabólitos, entre eles: magnésio (Mg2+), adenosina difosfato (ADP), fosfato inorgânico (Pi), amônia (NH3) e espécies reativas de oxigênio (ROS) 11 . Estratégias de recuperação com o objetivo da manutenção do desempenho têm sido amplamente estudadas [12][13][14][15] . Em especial a RA e RG (i.e.…”
Section: Discussionunclassified
“…74,75 Morrison et al 76 found that hyperthermia-induced inhibition of voluntary muscle activation was reversed with cooling, and other evidence shows that postexercise cooling had beneficial effects on performance during subsequent bouts of exercise. 77,78 Although further investigation is warranted to determine the exact mechanisms that act on improved performance after postexercise cooling, using cooling after exercise reduces the thermal load placed on the body and enhances the ability to recover.…”
Section: Discussionmentioning
confidence: 99%